Cell-free translation system from Drosophila S2 cells that recapitulates RNAi. - Wakiyama, M.; Kaitsu, Y.; Yokoyama, S. (Biochemical and Biophysical Research Communications, 2006)
RNA interference (RNAi) is a fundamental mechanism of gene regulation in a variety of organisms. In Drosophila cells, long double-stranded RNAs (dsRNAs) are processed into 21- to 23-nucleotide double-stranded fragments, termed short interfering RNAs (siRNAs). The siRNAs trigger sequence-specific mRNA degradation, which results in the inhibition of gene expression. These phenomena can be recapitulated in vitro in lysates of Drosophila syncytial blastoderm embryos. In the present work, we used the common Drosophila cell line, Schneider Line 2 (S2), as a source to establish a cell-free translation system. We demonstrate here that the S2 cell-free translation system can recapitulate RNAi. Both long dsRNAs and siRNAs can trigger RNAi in this system, and the silencing effects are significant. This system should provide an important tool for biochemical analyses of the RNAi mechanism.